(untitled) (Asian Journal of Medical and Biological Research, 2021)
Twenty-two rice lines were used to evaluate salt tolerance at the Laboratory of Biotechnology Division of Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh. Four SSR markers viz. AP3206f, RM1287, RM7075, and RM10793 were used to screen the germplasm for salt tolerance. SSR analysis revealed that the number of alleles per locus ranged from 3 to 5 with an average of 4.25 alleles per locus. Polymorphism Information Content (PIC) values ranged from 0.4762 (RM7075) to 0.7524 (AP3206f) with an average of 0.61 per locus. The highest genetic diversity (0.7810) was observed in loci AP3206f, and the lowest genetic diversity (0.5620) was observed in loci RM7075 with a mean diversity of 0.6663. The genotypes with genetic similarity clustered together in the dendrogram based on UPGMA method and we observed seven major clusters where cluster I contained most of the genotypes. Cluster I, II, III, IV, V, VI, and VII contained 6, 1, 2, 4, 4, 4 and 1 genotypes, respectively. These results revealed that marker AP3206f would be best in screening 22 rice genotypes followed by RM1287, RM7075, and RM10793 according to PIC values. These findings can have the potential role for further improvement of salinity tolerance rice genotypes through marker-assisted breeding. Asian J. Med. Biol. Res. 2021, 7 (2), 214-221